2010
DOI: 10.1186/gb-2010-11-7-r72
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA genes: conservation of sequence and brain expression among diverse amniotes

Abstract: Background: Long considered to be the building block of life, it is now apparent that protein is only one of many functional products generated by the eukaryotic genome. Indeed, more of the human genome is transcribed into noncoding sequence than into protein-coding sequence. Nevertheless, whilst we have developed a deep understanding of the relationships between evolutionary constraint and function for protein-coding sequence, little is known about these relationships for non-coding transcribed sequence. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(202 citation statements)
references
References 67 publications
8
192
0
2
Order By: Relevance
“…Twenty-nine (;5%) of the 550 zebra fish lincRNAs and 4.1 to 5.5% of the 3122 mouse lincRNAs were evolutionally conserved as measured by alignment of primary sequences, suggesting a rapid sequence evolution of lincRNAs (Ponjavic et al, 2007;Marques and Ponting, 2009;Ulitsky et al, 2011). Other studies, which used more comprehensive evolutionary analytical methods, reported a higher conservation rate (;11%) of lincRNAs in mouse (Guttman et al, 2009;Chodroff et al, 2010). The low level of evolutionary conservation of Arabidopsis lincRNA in primary sequence is consistent with that previously reported in mammals.…”
Section: Design Of An Identifier System Of Arabidopsis Lincrnasmentioning
confidence: 91%
“…Twenty-nine (;5%) of the 550 zebra fish lincRNAs and 4.1 to 5.5% of the 3122 mouse lincRNAs were evolutionally conserved as measured by alignment of primary sequences, suggesting a rapid sequence evolution of lincRNAs (Ponjavic et al, 2007;Marques and Ponting, 2009;Ulitsky et al, 2011). Other studies, which used more comprehensive evolutionary analytical methods, reported a higher conservation rate (;11%) of lincRNAs in mouse (Guttman et al, 2009;Chodroff et al, 2010). The low level of evolutionary conservation of Arabidopsis lincRNA in primary sequence is consistent with that previously reported in mammals.…”
Section: Design Of An Identifier System Of Arabidopsis Lincrnasmentioning
confidence: 91%
“…A recent study has also identified expressed orthologs of a few highly conserved and brain-expressed mouse lncRNAs in species as distant as opossums and chickens (Chodroff et al 2010). However, the number of human lincRNAs that have an orthologous, actively expressed, transcript in other species remains unknown.…”
Section: Expressed Syntenic Orthologs Of Human Lincrnas In Mammals Anmentioning
confidence: 99%
“…In contrast, other lncRNAs are evolutionarily conserved. Some orthologous lncRNAs exhibit similar expression patterns in the embryonic and postnatal brains of birds, marsupials, and eutherian mammals, implying that they have fundamental roles in brain development [13]. Furthermore, a large proportion of lncRNAs expressed in the developing brain are associated, because of their genomic context, with protein-coding genes known to play roles in neural Regulate other long and short non-coding RNAs at the epigenetic, transcriptional, and post-transcriptional level Serve as hosts for the biogenesis of certain short non-coding RNAs Act as microRNA sinks/sponges that bind to miRNAs, sequestering them away from their target mRNAs Bind to microRNA binding sites in mRNAs, masking these sites and preventing miRNA-mediated regulatory events Have dual roles as long non-coding RNA transcripts and as substrates for translation Nuclear architecture Act as scaffolds for the formation of subnuclear domains and their dynamic reorganization gene regulation and brain development.…”
Section: Brain Developmentmentioning
confidence: 99%
“…Data from animal models, as well as human tissues, reveals patterns that are regional; cell type-, subcellular compartment-, and developmental stagespecific; activity-dependent; and even sexually dimorphic [7,[10][11][12][13][14][15][18][19][20]]. An increasing number of studies are focused on interrogating the corresponding neurobiological roles played by these lncRNAs.…”
Section: Understanding the Biology Of Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation